Call For Preserving Cultural Identity In The Face Of Today's Threats - Jerzy Gocko (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Cultural identity can be analyzed from different perspectives: cultural and social anthropology, cultural studies, sociology and other human and cultural sciences. The present study undertakes a reflection on the cultural identity of man in the view of Catholic moral theology and, more precisely, on the factors that may induce its loss. In the first place, the author discusses the issue of contemporary religious indifferentism, read as a specific type of threat to human identity in vertical dimension. Religious indifferentism along with pluralism on axiological level are manifested as, to use the classification proper for classic aretology, a specific type of distortion of cultural identity per defectum, while fundamentalism and nationalism, described in the later part of the article, as distortion per excessum. Finally, the study presents the relationship between fidelity to cultural identity and deficits of modern democracy.